2017
DOI: 10.7567/jjap.56.07kb01
|View full text |Cite
|
Sign up to set email alerts
|

Study on effect of the surface variation of colloidal silica abrasive during chemical mechanical polishing of sapphire

Abstract: The surface and diameter size variations of colloidal silica particles during the chemical mechanical polishing (CMP) of sapphire substrates were investigated using different particle diameters of 20 and 55 nm. Dynamic light scattering (DLS) results show that the silica particles became larger after CMP under both conditions. The increase in particle size in the slurry was proportional to the material removal amount (MRA) as a function of the removed volume of sapphire substrates by CMP and affected the materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Some experimental reports have provided evidence that material was transferred from the upper silicon plate to the silica cluster. For example, Bun-Athuek et al [37] experimentally investigated changes in the surfaces and diameters of colloidal silica abrasives during the CMP of sapphire substrates. It was discovered that alumina elements from sapphire substrates dispersed in the used slurry and also aggregated on the surface of the abrasive after polishing when the diameter of the abrasive was 55 nm.…”
Section: Materials Removal Processmentioning
confidence: 99%
“…Some experimental reports have provided evidence that material was transferred from the upper silicon plate to the silica cluster. For example, Bun-Athuek et al [37] experimentally investigated changes in the surfaces and diameters of colloidal silica abrasives during the CMP of sapphire substrates. It was discovered that alumina elements from sapphire substrates dispersed in the used slurry and also aggregated on the surface of the abrasive after polishing when the diameter of the abrasive was 55 nm.…”
Section: Materials Removal Processmentioning
confidence: 99%
“…These results indicated that the downward force per particle (mechanical factor) is the dominant factor for polishing sapphire using silica particles with sizes of 20, 55, and 105 nm because the indentation ability of silica particles of 20 nm was lower than that obtained using the larger particles. 30,31) In the case where the ultrafine colloidal silica particles alone produced a very high MRR for sapphire, this indicated that chemical reactivity may be the main factor because small fine particles need a smaller activation energy to react with the sapphire substrate surface, as reported by Zhou et al 32) In addition, at the same slurry contents for the hybrid (2.5 mass % each of the ultrafine colloidal and large silica slurries, giving a total of 5 mass %) and single-sized (5 mass %) silica slurries, we found that the former abrasives gave larger MRRs for sapphire. The MRRs of sapphire obtained by mixing ultrafine silica particles into silica slurries with particle sizes of 20, 55, and 105 nm increased by about 85, 78, and 32%, respectively.…”
Section: Materials Removal Rate Of Sapphirementioning
confidence: 99%
“…Chemical mechanical polishing (CMP) technology, due to its ultrahigh accuracy and global planarization performance, is widely used in the LED substrates, high-end integrated circuits and medical device fields (Aida et al , 2021; Bun-Athuek et al , 2017;Krishnan et al , 2010). Polishing pad is one of the critical parts in CMP system, which has a direct influence on the workpiece surface quality (Kenchappa et al , 2021).…”
Section: Introductionmentioning
confidence: 99%